The relationship between dextranase enzyme in mouthwash and dental caries - Tongpong, Piyachat; Sirilun, Sasithorn; Chaiyasut, Chaiyavat; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Several studies reported that Thai people have oral health problems as a major problem. Therefore, care and treatment of oral health is an issue to be attentive. At the present, there are many products for oral and dental health care in many forms such as toothpaste, mouthwash, spray, deodorizing and inhibiting bacteria etc. Aims and Objective: This study investigated the effect of mouthwash containing Dextranase enzyme which affected to the changes of dental plaque (Plague Index) in eighteen dental caries volunteers by two mouthwash formulas; Formula I contained only Dextranase enzyme whereas Formula II contained a mixture of Nisin and Dextranase enzymes. Materials and Methods: This study was a single blind randomized clinical trial study. All participants were divided into two equal number of groups received mouthwash containing Dextranase enzyme or mouthwash containing a mixture of Nisin and Dextranase enzyme after using mouthwash. The study allowed participants to use mouthwash continuously for at least four weeks. The participants received oral examination, oral digital imaging and proximal radiographs using Bitewing oral Imaging method, respectively. Results: Both before and after using mouthwash were found to have dental caries. The study found that plague index in participants were decreased.Although the results of this study show that using mouthwash containing Dextranase enzymeeffect to decreased plaque accumulation on teeth volunteers were found to have dental caries but there are other factors besides the plaque on the teeththat causes dental cariese.g. susceptible tooth surface, Acidic product and pH change. Conclusion: Using mouthwash containing Dextranase enzyme help to reduce plaque formation.